The platform will undergo maintenance on Sep 14 at about 7:45 AM EST and will be unavailable for approximately 2 hours.
2017
DOI: 10.1080/00014788.2017.1303962
|View full text |Cite
|
Sign up to set email alerts
|

Why regulate private firm disclosure and auditing?

Abstract: Private firms face differing financial disclosure and auditing regulations around the world. In the United States and Canada, for example, private firms are generally neither required to disclose their financial results nor have their financial statements audited. By contrast, many firms with limited liability in most other countries are required to file at least some financial information publicly and are also required to have their financial statements audited. This paper discusses and analyzes the reasons f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

8
130
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 167 publications
(139 citation statements)
references
References 92 publications
8
130
0
1
Order By: Relevance
“…We define a private firm as one that has neither a publicly traded security nor a requirement to file reports with a financial market regulator, such as the SEC(Minnis and Shroff [2017]). The number of public companies is sourced from CRSP, while the number of private companies is the number of firms with at least 20 employees (followingDoidge et al [2017]) as reported by the Census Bureau's Business Dynamics Statistics public data set through 2014.2 These figures exclude firms from the Financial, Insurance, and Real Estate industries and other firms with data issues.…”
mentioning
confidence: 99%
“…We define a private firm as one that has neither a publicly traded security nor a requirement to file reports with a financial market regulator, such as the SEC(Minnis and Shroff [2017]). The number of public companies is sourced from CRSP, while the number of private companies is the number of firms with at least 20 employees (followingDoidge et al [2017]) as reported by the Census Bureau's Business Dynamics Statistics public data set through 2014.2 These figures exclude firms from the Financial, Insurance, and Real Estate industries and other firms with data issues.…”
mentioning
confidence: 99%
“…Accordingly, archival studies on the financial reporting of private firms (discussed in Sect. 3, below) have mostly focused on two issues that lend themselves to quantitative analysis: whether or when firms disclose financial statements (e.g., Minnis and Shroff 2017), and the 1 I use the terms "non-listed firms" and "private firms" synonymously. At the same time, it is important to differentiate between "private firms" and "family firms".…”
Section: Introductionmentioning
confidence: 99%
“…Such investigation may also assess the validity of thresholds based on metrics such as size, revenues, and employees for audit exemptions. Minnis and Shro (2017) provide interesting ideas for further studies. For instance, these authors claim there is a need for research providing evidence about the extent to which privately contracted auditors act as compliance monitors in various countries.…”
Section: Suggestions For Further Researchmentioning
confidence: 99%
“…A relatively small, but increasing number of studies have investigated these issues (e.g. Dedman, Kausar, & Lennox, 2014;Minnis & Shro , 2017).…”
Section: The Demand Side: Do Private Smes Demand Audit?mentioning
confidence: 99%